Amorphous carbon-coated prickle-like silicon of micro and nano hybrid anode materials for lithium-ion batteries - Kim, Jung Sub; Halim, Martin; Byun, Dongjin; Lee, Joong Kee (ELSEVIER, 2014)
Carbon coated prickle-like Si particles (PS@C) are prepared by metal-assisted chemical etching and subsequent coating with an amorphous carbon film carried out by thermal chemical vapor deposition (CVD). The electrochemical characteristics of PS@C employed as anode material for lithium-ion batteries are investigated in order to find a relationship between interfacial properties and electrochemical performance. The unique morphology of prickle-like Si (PS) having empty space can accommodate volume expansion during the lithiation and delithiation. Additionally, an amorphous carbon coating layer with a thickness of 10-15 nm deposited onto the PS prepared by thermal CVD is investigated as an effective way to enhance the cycle stability and rate capability of the PS electrode due to improved interfacial characteristics. The micro and nano hybrid structure of the PS material combined with the 12 wt.% amorphous carbon layer plays an important role in enhancing the electrochemical performance. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: PERFORMANCE; ELECTRODES; STORAGE; SURFACE; NANOCOMPOSITES